1983
DOI: 10.1115/1.3227415
|View full text |Cite
|
Sign up to set email alerts
|

Flow Distributions and Discharge Coefficient Effects for Jet Array Impingement With Initial Crossflow

Abstract: Two-dimensional arrays of circular air jets impinging on a surface parallel to the jet orifice plate are considered. The jet flow, after impingement is constrained to exit in a single direction along the channel formed by the jet orifice plate and the impingement surface. In addition to the crossflow which originates from the jets following impingement, an initial (independent) crossflow is present which approaches the array through an upstream extension of the channel. The configurations considered are intend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…6). Nonetheless, Florschuetz and Isoda (1983) have shown that for AP/P < 0.20-0.30 this procedure gives pressure loss predictions in excellent agreement with experiments; this assurance suffices the scope of this work, because situations requiring higher pressure drops have little practical applications in gas turbine cooling. 3.7 Typical gas turbine conditions Tab.…”
Section: Pressure Dropssupporting
confidence: 52%
See 2 more Smart Citations
“…6). Nonetheless, Florschuetz and Isoda (1983) have shown that for AP/P < 0.20-0.30 this procedure gives pressure loss predictions in excellent agreement with experiments; this assurance suffices the scope of this work, because situations requiring higher pressure drops have little practical applications in gas turbine cooling. 3.7 Typical gas turbine conditions Tab.…”
Section: Pressure Dropssupporting
confidence: 52%
“…12). - Florschuetz and Isoda (1983) and Florschuetz, Metzger and Su (1984) analyzed the effects of non-zero initial crossflow, a situation corresponding to the midchord region, where jets are crossed by spent flow coming from the leading edge ( Fig. 2).…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…An explanation for this type of behavior was originally presented in some detail in connection with noninitial crossflow test x/L Fig. 12 Effect of initial crossflow on jet array flow distribution for B(5,8,3)I geometry -experimental data compared with predictive model [12].…”
Section: Resultsmentioning
confidence: 99%
“…Outputs revealed that the previous numerical results had a good agreement with the experimental data at a low range of Reynolds numbers. Florschuetz et al [8][9][10] performed experimental work and theoretical analysis to study the effect of heat transfer performance for nozzle array impingement with the cross-flow on a flat test plate. The results confirmed that the crossflow decreased the performance of heat transfer.…”
Section: Introductionmentioning
confidence: 99%